2013
DOI: 10.2174/1876386301306010176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pain Catastrophizing in the Prediction of Acute and Chronic Postoperative Pain

Abstract: Background and Objectives: Despite the established association between greater pain catastrophizing and enhanced postoperative pain, it is still unclear: (i) what is the relative contribution of each of the pain catastrophizing scale (PCS) dimensions in the prediction of acute and chronic postoperative pain; and (ii) whether PCS scores mediate the association between acute and chronic postoperative pain intensity. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In the current study the rumination subscale, one component of catastrophizing, added to anxiety in the prediction of APSP intensity. This supports previous findings, namely on thoracotomy, 35 in which the unique role of rumination in APSP as well as CPSP prediction was highlighted. Additionally, other studies also showed that the rumination subscale was the most important catastrophizing component related to pain experience, with a higher predictive value compared with magnification and helplessness dimensions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study the rumination subscale, one component of catastrophizing, added to anxiety in the prediction of APSP intensity. This supports previous findings, namely on thoracotomy, 35 in which the unique role of rumination in APSP as well as CPSP prediction was highlighted. Additionally, other studies also showed that the rumination subscale was the most important catastrophizing component related to pain experience, with a higher predictive value compared with magnification and helplessness dimensions.…”
Section: Discussionsupporting
confidence: 92%
“…Another psychological factor, pain catastrophizing, has been recognized as a key predictor for a wide range of pain-related outcomes, 15,41,51,[62][63][64] including APSP and CPSP after a variety of surgeries, 17,25,[33][34][35]48,49,57,58,65 although no study has evaluated its influence on inguinal hernioplasty. In the current study the rumination subscale, one component of catastrophizing, added to anxiety in the prediction of APSP intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain catastrophizing is negatively magnifying an actual pain or expected experience. A study showed that catastrophizing, as a mediating variable, causes chronic pain in patients who use it as a defense mechanism (7). According to the fear-avoidance model, pain catastrophizing, as the first variable after experiencing pain, leads to the fear of pain, vigilance to pain, avoidance behaviors, disability, and ultimately more pain perception (8).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was suggested as patients without pain show fewer catastrophizing thoughts than those in pain. 10,14,18 However, few studies compared individuals with different clinical conditions, 8,19,20,21 and only one study compared catastrophizing scores among samples of patients without pain, with acute pain, and with chronic pain. 19 However, the authors 19 considered the global score for catastrophizing, without analyzing its components.…”
Section: Introductionmentioning
confidence: 99%